Differences in basic elements between juniors and seniors and between women and men in gymnastics - Krug, J.; Knoll, Kl.; Wagner, R.; Bronst, A. (1998)
The scientists made a comparative analyses between women and mens well as between seniors and juniors regarding the level of difficulty and the level of sports technique.